Intraoperative Frozen Section Assessment of Sentinel Lymph Node Biopsy in Breast Carcinoma to Determine the Axillary Lymph Node Status - Soni, Ramawatar R; Bhongade, Aishwarya Vinod; Deshmukh, Anil T; Arora, Rajendrasingh S; Nomaan, Nafees; Dagdiya, Kirti S (Annals of Pathology and Laboratory Medicine, 2018)
BACKGROUND: Breast cancer is commonest malignancy of females all over the world. Modified radical mastectomy is still considered as a standard for treating breast cancers. Axillary lymphadenectomy is achieved at the cost of significant morbidity, with a high acute complication rate and a high chronic lymphedema rate. Sentinel lymph node biopsy is associated with better arm function, better quality of life, a shorter hospital stay, and faster recommencement of daily activities than standard axillary lymph node dissection. There are inconsistencies and controversies regarding the pathological work-up of sentinel lymph nodes and no generally applied guidelines exist. METHODS: In total, 60 breast carcinoma cases were studied over a period of 2 years. The axillary lymph node status was determined intra-operatively in carcinoma breast by frozen section assessment of sentinel lymph node. RESULTS: Intraoperative frozen section had sensitivity of 90.3%, specificity of 100%, positive predictive value of 100%, negative predictive value of 90.6% and diagnostic accuracy of 95%. The sentinel lymph node biopsy had a false negative rate of 13.3%. 16.1% cases showed only sentinel lymph node positivity with non-sentinel lymph nodes free from metastasis. The positivity of sentinel lymph node for metastasis was dependent upon certain characteristics of patients such as tumour size, tumour location and grade of tumour and was independent of patient’s age. CONCLUSION: Intraoperative frozen section evaluation of sentinel lymph node (SLN) to predict the status of non-SLN can be recommended only in selected patients in early stage of disease.